STRATEGI EXPERIENTIAL MARKETING BRAND LOKAL TAKA CRAFT (Studi Kasus Custom Workshop Taka Craft) - Rakan Adiantoro (2020)
This study aims to analyze the Taka Craft Local Brand Experential Marketing Strategy with a Custom Workshop as the study case. This study aims to find out the reasons and strategies of Taka Craft in its Experential Marketing through a Custom Workshop. This study uses the SOSTAC Model to analyze the strategies used by Taka Craft in the Custom Workshop. The research approach used in this research is a descriptive qualitative approach with a case study method. This research was conducted by interviewing informants and key informants from Taka Craft consisting of Owner, Crew and Consumers. In addition, a literature study was also carried out in this research.